تحرّي تعبيرية بروتين الـβ-Catenin في سوء التصنّع البشروي الفموي - بركات, شريف; نصر, علاء (Latakia University Journal -Medical Sciences Series, 2016)
تعتبر آفات سوء التصنّع الفمويّة في كثير من حالاتها آفات ما قبل سرطانيّة، وتقوم الخلايا الظهاريّة السرطانية بالغزو والاستعمار من خلال آليّة التحوّل الظهاري الميزانشيمي. وقد أجريت هذه الدراسة لتحرّي التحوّل الظهاري الميزانشيمي عبر دراسة تغيرات الـβ-catenin في الدرجات المختلفة لسوء التصنّع البشروي الفموي.تمّ دراسة 45 خزعة مثبّتة بالفورمالين ومدمجة بشمع البارافين مؤرشفة ومشخّصة على أنّها أفات ذات سوء تصنّع بشروي فموي، وتمّ تقطيعها وتلوينها بالـ H&E ثمّ تقييم درجة سوء تصنّعها وتقسيمها لثلاث مجموعات حسب درجة سوء التصنّع، ثمّ لوِّنت بالملوّن المناعي الكيميانسيجي β-catenin لدراسة التحول الظهاري الميزانشيمي فيها. وتم مقارنتها مع عينة شاهدة من نسج فموية سليمة.واستنتج أنهيزداد معدّل التحوّل الظهاري الميزانشيمي مع زيادة درجات سوء التصنّع. ويزداد معدّل التطفُّر في البروتينات التي تضبط مستويات الـ β-cateninمع زيادة درجات سوء التصنّع. فبالتالي يمكن استخدام الملون المناعي الكيميانسيجي الـ β-cateninللتنبّؤ باحتماليّة التحوّل الخبيث للآفات الفمويّة البشرويّة.Oral epithelial dysplasia is a precancerous change develops in the oral mucosa, and leukoplakia is the most common precancerous lesions in oral mucosa.The epithelial-mesenchymal transition (EMT) is considered the mechanism through which the oral leukoplakia becomes malignant, and it's also responsible for the invasion and metastasis of cancers. This study investigates the expression of β-catenin in epithelial-mesenchymal transition detected by immunohistochemical staining in the different grades of oral epithelial dysplasia.The sample consisted of 45 formalin-fixed, paraffin-embedded specimens of oral leukoplakia with different grades of oral epithelial dysplasia; specimenswere immunohistochemically stained with β-catenin antibody.The control group was consisted of biopsies from the normal oral epithelia.The EMT rates are associated with the severity of the oral epithelial dysplasia.That means, the epithelial-mesenchymal transition marker β-catenin could be used to evaluate the potentiality of malignant transformation in the precancerous lesions.